Investigating the relationship between optimism and stress responses: A biopsychosocial perspective. (15th July 2018) - Baumgartner, Jennifer N.; Schneider, Tamera R.; Capiola, August
Abstract: We investigated the relationship between optimism and psychological, behavioral, and psychophysiological stress responses. We expected that optimism would relate to challenge appraisals, more positive and less negative affect, better performance, and challenge physiological patterns. 153 participants reported their stressor appraisals and state affect regarding an impending stressor. Performance and cardiovascular reactivity were measured during the stressor. We replicated past research showing that challenge appraisals predict more positive and less negative affect, better performance, and cardiovascular reactivity. We extend past research showing that optimism predicts challenge appraisals and less negative affect, but not positive affect, performance, or cardiovascular reactivity. This research revealed some psychological benefits of optimism for acute stressors, which have also been found for chronic stressors. Highlights: Replicates challenge/threat patterns for affect, performance, and physiology Examines the association of optimism with biopsychosocial stress responses Optimism relates to some aspects of challenge responses patterns, but not others. Complements and extends research on optimism and chronic stress